Two-dimensional video gait analyses in patients with congenital insensitivity to pain. (August 2013) - Zhang, Yasu; Ogata, Naoshi; Yozu, Arito; Haga, Nobuhiko
<x xml:space="preserve">Abstract</x> Purpose: To clarify the features of gait in patients with congenital insensitivity to pain (CIP) by analyzing the video-recorded gait. Methods: Eleven patients with the diagnosis of hereditary sensory and autonomic neuropathy (HSAN) type 4 or 5 and 15 healthy participants were enrolled in this study. Gait was analyzed using two-dimensional (2D) digital video and video analysis software. Walking speed, cadence, step length, stance phase duration, and heel contact to foot flat period were compared between patients and healthy participants. Results: The results showed that walking speed and heel contact angular velocity were significantly higher (p < 0.05), and step length was significantly longer (p < 0.05) in CIP patients, especially in the younger age group. Conclusion: Young patients with CIP walked faster, with a longer step length and higher heel contact angular velocity than young control participants. These results may explain the frequency of lower extremity injuries in CIP patients.